2011
DOI: 10.1038/cddis.2011.72
|View full text |Cite
|
Sign up to set email alerts
|

Gene-dependent cell death in yeast

Abstract: Caspase-dependent apoptotic cell death has been extensively studied in cultured cells and during embryonic development, but the existence of analogous molecular pathways in single-cell species is uncertain. This has reduced enthusiasm for applying the advanced genetic tools available for yeast to study cell death regulation. However, partial characterization in mammals of additional genetically encoded cell death mechanisms, which lead to a range of dying cell morphologies and necrosis, suggests potential appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 40 publications
3
74
0
Order By: Relevance
“…Number of genes with a phenotype in each of these studies and that displayed increased susceptibility (A) or resistance (B) to acetic acid in our study. Genes with common phenotypes between the studies of Teng et al [45], Mira et al [16] and Kawahata et al [15] are not evidenced in the representation. The numbers in the centre of “Our results” circles represent the number of genes found exclusively in our screen.…”
Section: Resultsmentioning
confidence: 99%
“…Number of genes with a phenotype in each of these studies and that displayed increased susceptibility (A) or resistance (B) to acetic acid in our study. Genes with common phenotypes between the studies of Teng et al [45], Mira et al [16] and Kawahata et al [15] are not evidenced in the representation. The numbers in the centre of “Our results” circles represent the number of genes found exclusively in our screen.…”
Section: Resultsmentioning
confidence: 99%
“…Cell death screens of the entire ~5,000 unique knockout strains in the yeast knockout collection revealed over 800 candidate genes, when deleted, result in two-fold or better survival following exposure to a heat ramp stimulus, or to acetate concentrations compared to the wild type strains [2, 76]. Based on 1-2 month evolution experiments, cell death mechanisms are required for long-term survival of single-cell species, for example, to reduce the population to a size that is sustainable on the available resources [77].…”
Section: How Did Pcd Evolve?mentioning
confidence: 99%
“…This assay is based on the viability of yeast knockout strains after treatment with precisely regulated heat ramp stimuli (a condition mild enough to allow time for gene-dependent cell death to occur but prior to adaptation), regardless of the cell morphologies during the dying process [80]. By applying this assay to the yeast knockout collection, we found unexpectedly that many gene knockout strains (~40%) are more resistant to cell death compared to the parental wild type strain [2]. This suggested that many genes can contribute to cell suicide when the environmental temperature is increased gradually [2].…”
Section: How Did Pcd Evolve?mentioning
confidence: 99%
See 2 more Smart Citations